Endemic fungal infections in solid organ transplant recipients—Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice. Issue 9 (23rd April 2019) - Miller, Rachel; Assi, Maha; ,
Abstract: These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention and management of blastomycosis, histoplasmosis, and coccidioidomycosis in the pre‐ and post‐transplant period. Though each of these endemic fungal infections has unique epidemiology and clinical manifestations, they all share a predilection for primary pulmonary infection and may cause disseminated infection, particularly in immunocompromised hosts. Culture remains the gold standard for definitive diagnosis, but more rapid diagnosis may be achieved with direct visualization of organisms from clinical specimens and antigen‐based enzyme immunoassay assays. Serology is of limited utility in transplant recipients. The mainstay of treatment for severe infections remains liposomal amphotericin followed by a step‐down azole therapy. Cases of mild to moderate severity with no CNS involvement may be treated with azole therapy alone. The newer generation azoles provide additional treatment options, but supported currently with limited clinical efficacy data. Azole therapy in transplant recipients presents a unique challenge owing to the drug‐drug interactions with immunosuppressant agents. Therapeutic drug monitoring of azole levels is an essential component of effective and safe therapy. Infection prevention centers around minimizing epidemiological exposures, early clinical recognition, and azole prophylaxis in selected individuals.